Evaluasi dan Perbaikan Alur dan Navigasi Website SMA Negeri 4 Banjarmasin Menggunakan Pendekatan Human Centered Design (HCD) - Intan Rahmawati; Hanifah Muslimah Az-zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Senior High School 4 Banjarmasin was established by 1977. This school has a website for delivering information about the school. Based on the interview from users and stakeholders, there are some problems in getting information, providing unstructured information layout, as well as categorizing and content naming. These problems make users have a hard time finding information, so there is a need to be a solution. Evaluating the flow and navigation is the answer, by using Tree Testing method and measuring aspects on success rate, directness, first click, and destination to find the core of the problems. This project uses the Card Sorting Test method in making information structure from the website by making changes according to users' and stakeholder's needs. This project also uses Human Centered Design (HCD) approach in obtaining useful improvements and sitemaps. The rules are from usability guidelines and website that supports in making solution designs. The result of this study produces recommendations for improvements in flow and navigation according to users' needs with stakeholders' approval and provides improvement evaluation scores for measured aspects.